Association of anti-sperm antibodies with chronic prostatitis: A systematic review and meta-analysis. (November 2016) - Jiang, Yumei; Cui, Dong; Du, Yuefeng; Lu, Jun; Yang, Lin; Li, Jinmei; Zhang, Jing; Bai, Xiaojing
Highlights: The literature searches of our article were comprehensive. Meta-analysis was performed to evaluate the correlation of ASA and chronic prostatitis. Our study illustrates that there have significant correlation between ASA and Chronic prostatitis. Our results might shed valuable insights into the relationship between chronic prostatitis and male reproduction. Abstract: Chronic prostatitis is a risk factor for impaired male fertility potential, and anti-sperm antibodies (ASAs) cause the autoimmune disease immune infertility, which has a negative effect on semen parameters. Current studies have investigated the ASA-positive relationship between chronic prostatitis versus normal controls, but have shown inconsistent results. Hence, we systematic searched the PubMed, EMBASE, Science Direct/Elsevier, Medline, and the Cochrane Library up to October 2015 for case-control studies that involved the ASA-positive relationship between chronic prostatitis patients versus normal controls. The meta-analysis was performed with Review Manager and Stata software. After literature search, six studies were identified, including 721 cases of chronic prostatitis and 160 normal controls. Our results illustrated a significant correlation of the ASA-positive relationship between chronic prostatitis patients versus normal controls. The combined odds ratio of the ASA-positive rate in chronic prostatitis patients and normal controls was 3.26 (1.86–5.71). There was also a significant correlation of the ASA-positive relationship between National Institutes of Health (NIH) III versus normal controls, and the combined OR was 2.46 (1.10–5.51). However, there was no significant correlation of the ASA-positive relationship between National Institutes of Health (NIH) II versus normal controls. The present study illustrates that the positive rate of ASAs in chronic prostatitis patients was significantly higher than in the control group, suggesting that chronic prostatitis has a negative effect on male reproductive function. However, studies with larger samples are needed to better illuminate the correlation between ASAs and chronic prostatitis.